Regional Economic Transformation: The role of clusters in specialised diversification - Jonatan Paton; Jaime Del Castillo; Belen Barroeta (European Regional Science Association (ERSA), 2014)
Regarding context conditions and the role of territories on competitiveness and innovation, clusters have become progressively a spreading phenomenon all around the world. Recently, the importance of clusters has been mixed with the concept of smart specialization, a territorial development model that seeks to increase the efficiency and effectiveness of economic systems with the aim of contributing to sustainable development. This new model has been strongly incorporated within the new Regional Policy logic defined by the European Commission for the period 2014-2020, in the shape of the upcoming Regional Smart Specialisation Strategies ?RIS3. The aim of this article is to analyse the concept of both cluster and smart specialization form a twofold perspective: the economic development theoretical approach and the policy perspective. In other words, the implications of new RIS3 strategies regarding clusters, and vice versa, as well as their role as policy instruments. To do so, the first chapter introduces briefly the traditional cluster approach, differentiating the development model behind it, as well as the cluster policy dimension that has led to the explosion of cluster initiatives around the world. The second chapter introduces the relationship between the clusters and the new smart specialization development model as two perspectives that mutually reinforce and share common elements that contribute one to another. The third chapter analyses deeply the potential involvement of cluster initiatives and cluster policies within the upcoming smart specialisation strategies that are being fostered by the European Commission for the new programming period 2014-2020. The fourth chapter analyses all these elements regarding clusters and smart specialisation into the Basque Country case, a region with a cluster policy since the 90s and where a reflection must be done regarding the upcoming RIS3. According to the results obtained Basque clusters seem to be drivers for higher productivity and exports, being interesting to consider them as catalysts for contributing to smart specialization principles higher degrees of specialization and open economy. In addition to these, they also could be the key for the third theme in a RIS3 focused on specialised diversification through related variety exploitation and entrepreneurial discoveries. Finally, from the results from the Basque case, a fifth chapter adds a number of generalised recommendations about how to reformulate cluster policies regarding smart specialisation model and the likely role of cluster initiatives within the new governance system that regions probably develop under smart specialisation strategies.
Keywords: O33; 330; Technological Change: Choices and Consequences; Diffusion Processes